Influence of Hydroxypropyl-β-Cyclodextrin on the Photostability of Fungicide Pyrimethanil - Carlos Fernandes; Igor Encarnação; Alexandra Gaspar; Jorge Garrido; Fernanda Borges; E. Manuela Garrido (International Journal of Photoenergy)
Pesticides continue to play an important role in pest management. However, the intensive pesticide application has triggered several environment negative effects that cannot be disregarded. In this study, the inclusion complex of pyrimethanil with HP-β-CD has been prepared and characterized by proton nuclear magnetic resonance spectroscopy. The formation of the pyrimethanil/HP-β-CD inclusion complex increased the aqueous solubility of this fungicide around five times. To assess the influence of microencapsulation on the environmental photostability of the fungicide, the photochemical degradation of pyrimethanil and pyrimethanil/HP-β-CD inclusion complex has been investigated in different aqueous media such as ultrapure and river water under simulated solar irradiation. The studies allow concluding that pyrimethanil/HP-β-CD inclusion complex increases significantly the photostability of the fungicide in aqueous solutions, especially in natural water. Actually, the half-life of pyrimethanil/HP-β-CD inclusion complex was increased approximately by a factor of four when compared to the free fungicide. The overall results point out that pyrimethanil can be successfully encapsulated by HP-β-CD, a process that can improve its solubility and photostability properties.